The Da'wah Method of Kiyai Haji Muhammad Rahmat Najieb in the Context of Reform in the Mosque of the Central Leadership of the Islamic Union - Muhammad Mufti Sulthanan Nasira; Dadan Suherdiana; Rojudin Rojudin (Journal Of Social Science (JoSS), 2025)
The purpose of this research is to find out the method of preaching al-hikmah, the method of preaching mauidzhah hasanah, the method of preaching al-mujaadalah is used by Kiyai Haji Muhammad Rahmat Najieb in spreading religious purification (renewal) in studies at the PP Persis Mosque. The research method used is qualitative with a descriptive approach, the data collection technique is in the form of interviews, observation, and documentation. The results of this research are that study conducted by him at the PP Persis Mosque has three types including the study of interpretation of ibn katsir, the study of interpretation an-nur, and the study of the bulughul maram book using the al-hikmah method in the form of stories, the mauidzhah hasanah method in the form of advice, and the al-mujaadalah method is in the form of discussion.